Avenues for Peer Development in Cross-subject Teams - Valiukienė, Roma (Verbum, 2013)
The current tendency to promote university teacher’s research capacities has long over-shadowed the demand for high-quality teaching and made educator’s human capital and professional intellect look insignificant and not appreciated. Moreover, though it is commonly recognised that co-operative strategic intelligence creates most of the professional intellect of an organization, some are dubious about the value of collaborative educator work in a university for the benefit of students and the reputation of the institution itself. The paper shares insights into how to boost the teacher’s confidence in self and others, and what affects such cultivated self-esteem would have in modern needs-based cross-cultural training environments. The reflections are based on the experiences in the CLIL project implemented by the Institute of Foreign Languages of Vilnius University, and comparisons are made regarding the purposes and ways of collaboration between subject and language teachers in secondary schools and universities. In addition, an analysis of the most interesting accomplishments and an overview of key learning experiences are shared for a development of similar projects in future. To place the experience in a broader context, observations are causally linked with the overall situation in higher education where a gradual shift away from conventional teaching methods to more unstructured, learner-centred programmes is being made.
Keywords: collaborative work; professional intellect; creativity; innovation; teaching culture